Time-resolved operando studies of carbon supported Pd nanoparticles under hydrogenation reactions by X-ray diffraction and absorption. (7th June 2018) - Bugaev, Aram L.; Usoltsev, Oleg A.; Lazzarini, Andrea; Lomachenko, Kirill A.; Guda, Alexander A.; Pellegrini, Riccardo; Carosso, Michele; Vitillo, Jenny G.; Groppo, Elena; van Bokhoven, Jeroen A.; Soldatov, Alexander V.; Lamberti, Carlo
Abstract : We present a comprehensive study of a 5 wt% Pd/C catalyst in various environments by using in situ and operando X-ray absorption and diffraction. Abstract : The formation of palladium hydride and carbide phases in palladium-based catalysts is a critical process that changes the catalytic performance and selectivity of the catalysts in important industrial reactions, such as the selective hydrogenation of alkynes or alkadienes. We present a comprehensive study of a 5 wt% carbon supported Pd nanoparticle (NP) catalyst in various environments by using in situ and operando X-ray absorption spectroscopy and diffraction, to determine the structure and evolution of palladium hydride and carbide phases, and their distribution throughout the NPs. We demonstrate how the simultaneous analysis of extended X-ray absorption fine structure (EXAFS) spectra and X-ray powder diffraction (XRPD) patterns allows discrimination between the inner "core" and outer "shell" regions of the NP during hydride phase formation at different temperatures and under different hydrogen pressures, indicating that the amount of hydrogen in the shell region of the NP is lower than that in the core. For palladium carbide, advanced analysis of X-ray absorption near-edge structure (XANES) spectra allows the detection of Pd–C bonds with carbon-containing molecules adsorbed at the surface of the NPs. In addition, H/Pd and C/Pd stoichiometries of PdH x and PdC y phases were obtained by using theoretical modelling and fitting of XANES spectra. Finally, the collection of operando time-resolved XRPD patterns (with a time resolution of 5 s) allowed the detection, during the ethylene hydrogenation reaction, of periodic oscillations in the NPs core lattice parameter, which were in phase with the MS signal of ethane (product) and in antiphase with the MS signal of H2 (reactant), highlighting an interesting direct structure–reactivity relationship. The presented studies show how a careful combination of X-ray absorption and diffraction can differentiate the structure of the core, shell and surface of the palladium NPs under working conditions and prove their relevant roles in catalysis.